Development of Electronic Teaching Modules Using Flip Books in Internet of Things (IoT) Subjects at SMK Negeri 6 Kupang - Ine Nua, Yasinta Febrianti; Neno, Khatrin J. Taku; Benufinit, Yonly A. (JUPE : Jurnal Pendidikan Mandala, 2024)
“Development of Electronic Teaching Modules on Internet Of Things (Iot) Subjects at Smkn 6 Kupang”. Informatics Education Study Program, Faculty of Teacher Training and Education, Citra Bangsa University Kupang. Advisor 1: Khatrin J. Taku Neno, S.Pd.Kom., M.Pd, Advisor 2: Yonly A. Benufinit S.Kom., MT.This thesis discusses the development of electornik teaching modules using the flipbook application. The purpose of this research is to produce a web-based electornik teaching module to facilitate students in independent and guided learning equipped with instructions for self-study, so that students can learn according to their abilities and can fulfill all the competencies that students must master in internet of thinks subjects. the type of research used in this research is R&D with Quantitative data analysis techniques using ADDIE mode. To measure the success of this electornik teaching module obtained by distributing questionnaires to media experts, material experts and to the main subjects in this study, namely students, as for the final results of this study which show the success of this research is the first media expert the value obtained from the assessment of the first media expert is 91%, the second media expert the value of money obtained is 97% while for the main subject, namely students, the results of the validation of the product feasibility questionnaire from students with an average value of 90.76% This indicates that the teaching module developed has met the expected quality standards from various aspects.